Preparation and application of a heavy-duty anti-corrosion petroleum pipeline powder coating

By using powder coatings composed of modified zirconium phosphate composite and two-step epoxy resin, the corrosion problem of petroleum pipelines is solved, high adhesion and wear resistance are achieved, and the corrosion resistance is significantly improved, and the oil is protected. The pipe also extends its service life.

CN118516028BActive Publication Date: 2025-01-07HUBEI RUIZHI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410495499.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-01-07
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

During the use of oil pipelines, chemical and electrochemical reactions often cause corrosion, affecting performance and life, and may leak harmful substances and pollute the environment. It is difficult for existing coatings to take into account excellent corrosion protection and mechanical properties.

Method used

Powder coatings composed of two-step epoxy resin, phenol curing agent, dimethylimidazole, leveling agent, gloss enhancer, degassing agent, wollastonite and modified zirconium phosphate composite, etc., through specific The ratio and treatment method are prepared to form a coating with excellent adhesion and wear resistance.

Benefits of technology

The coating exhibits high adhesion and wear resistance in high temperature and chemical corrosion environments, effectively protects oil pipelines, extends its service life, and remains stable in a variety of solutions and environments, significantly improving the anti-corrosion effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of coatings, and in particular to the preparation and application of a heavy-duty anti-corrosion petroleum pipeline powder coating. The present invention uses zirconium phosphate and halloysite to be treated with hydrogen peroxide and an inorganic acid aqueous solution, and then treated with a treatment medium composed of γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and an ethanol aqueous solution, and then post-processed to obtain an anti-corrosion factor, which is prepared with a two-step epoxy resin, a phenolic curing agent, dimethylimidazole, a leveling agent, a brightener, a degassing agent, wollastonite and a pigment to obtain a powder coating; the coating has excellent wear resistance and adhesion, good mechanical properties, and also has a strong anti-corrosion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to the preparation and application of a heavy-duty anti-corrosion petroleum pipeline powder coating. Background Art

[0002] The oil pipelines and equipment used in the oil extraction process are often made of oil metal materials, which often corrode during use. This type of corrosion problem is mostly caused by chemical reactions and electrochemical reactions, which seriously affects the performance and life of the metal materials, and also has a very adverse impact on the oil production and transportation work. When toxic, flammable and explosive oil pipelines and equipment are severely corroded, it may lead to the leakage of harmful substances, pollute the natural ecological environment, and pose a greater threat to people's lives and safety. Therefore, it is very necessary to carry out anti-corrosion treatment on oil pipelines and equipment in the oil extraction industry.

[0003] Powder coating is a kind of micro powder coating without organic solvents. It has the characteristics of less pollution, convenient coating and processing, excellent performance, and has a protective effect on equipment. Among them, epoxy type powder coating is a powder coating made of epoxy resin as the base material, with fillers, curing agents, anti-corrosion raw materials and other ingredients added. It has good corrosion resistance and is often used in the anti-corrosion treatment of oil pipelines and equipment.

[0004] Since oil pipelines are often laid in harsh environments, the coatings used in oil pipelines are not only required to have good anti-corrosion properties, but also have high requirements for mechanical properties such as coating adhesion and strength. Therefore, researching a powder coating for oil pipelines that has both excellent anti-corrosion and mechanical properties is one of the technical problems that need to be solved at present. Summary of the invention

[0005] The present invention aims at the problems pointed out in the above background technology, and proposes a solution of the present invention. The present invention discloses the preparation and application of a heavy-duty anti-corrosion petroleum pipeline powder coating.

[0006] Specifically, the technical solution of the present invention is as follows:

[0007] On the one hand, the present invention provides a heavy-duty anti-corrosion petroleum pipeline powder coating, the preparation raw materials of which include two-step epoxy resin, phenolic curing agent, dimethylimidazole, leveling agent, brightener, degassing agent, wollastonite, anti-corrosion factor and pigment.

[0008] In the powder coating of the present invention, the mass dosage of the two-step epoxy resin can be 550-750 parts, 600-700 parts or 600-660 parts. When the two-step method is used to synthesize the epoxy resin, the reaction is carried out in a homogeneous phase, the chain growth reaction is relatively stable, so the obtained resin has a narrow relative molecular mass distribution, a low organic chlorine content, and the epoxy value and softening point can be controlled and adjusted by the ratio and reaction temperature. It has the advantages of simple process, convenient operation, less equipment, short working hours, no three wastes, one-time reaction, and easy control and adjustment of product quality.

[0009] In the powder coating of the present invention, the mass amount of the phenolic curing agent can be 100-170 parts, 120-160 parts or 130-150 parts. The phenolic curing agent is at least one of diphenolyl propane, 2,4,6-tris(dimethylaminomethyl)phenol, p-diphenol, m-diphenol, bisphenol F diglycidyl ether, bisphenol A, resorcinol and catechol resorcinol.

[0010] In the powder coating of the present invention, the weight amount of dimethylimidazole can be 2-10 parts, 2.5-8 parts, or 3-5 parts.

[0011] In the powder coating of the present invention, the mass amount of the leveling agent can be 5-15 parts, 5.5-10 parts, 6-8 parts. The leveling agent includes at least one of silicone, acrylate, and fluorocarbon. The leveling agent of the present invention can also be selected from the German BYK type, such as BYK-371, BYK-346, BYK-307, BYK-310, BYK-381, BYK-333, etc.

[0012] In the powder coating of the present invention, the mass amount of the brightener can be 1-8 parts, 2-7 parts, 3-5 parts. The brightener of the present invention can be selected from brightener Ranbar OB-LA, Shin-Etsu KP-366, brightener SYZ-6701B, brightener ZR-Z701, etc.

[0013] In the powder coating of the present invention, the mass amount of the degassing agent can be 1-5 parts, 1.5-4.5 parts, 2-4 parts. The degassing agent of the present invention can be selected from polyamide wax NEW-0400, degassing agent KT961, etc.

[0014] In the powder coating of the present invention, the mass amount of wollastonite can be 150-300 parts, 160-250 parts, or 180-240 parts. The wollastonite used in the present invention can be a common wollastonite product obtained in a commercial manner, for example, from Shandong Wenqi New Materials Co., Ltd.

[0015] In the powder coating of the present invention, the mass amount of the anticorrosive factor can be 8-40 parts, 10-30 parts, or 12-25 parts.

[0016] In the powder coating of the present invention, the weight amount of the pigment can be 50-200 parts, 90-190 parts, 80-180 parts. The pigment used in the present invention includes at least one of titanium dioxide, zinc oxide, lithopone, red iron oxide, toluidine red, scarlet powder, and cadmium red.

[0017] Furthermore, the coating of the present invention comprises the following parts of preparation raw materials: 550-750 parts of two-step epoxy resin, 100-170 parts of phenolic curing agent, 2-10 parts of dimethylimidazole, 5-15 parts of leveling agent, 1-8 parts of brightener, 1-5 parts of degassing agent, 150-300 parts of wollastonite, 8-40 parts of anticorrosive factor and 50-200 parts of pigment.

[0018] Furthermore, the coating of the present invention comprises the following parts of preparation raw materials: 600-660 parts of two-step epoxy resin, 130-150 parts of phenolic curing agent, 3-5 parts of dimethylimidazole, 6-8 parts of leveling agent, 3-5 parts of brightener, 2-4 parts of degassing agent, 180-240 parts of wollastonite, 12-25 parts of anticorrosive factor and 80-180 parts of pigment.

[0019] Furthermore, the anti-corrosion factor is obtained by treating zirconium phosphate and halloysite with hydrogen peroxide and an aqueous solution of an inorganic acid, and then treating it with a treatment medium composed of γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and an aqueous solution of ethanol, and then post-treating it.

[0020] Furthermore, the preparation method of the preservative factor comprises the following steps:

[0021] S1, mixing zirconium phosphate, halloysite, hydrogen peroxide, and an inorganic acid aqueous solution, filtering, drying, and crushing the filtered solid to obtain a zirconium phosphate and halloysite composite;

[0022] S2, stirring and mixing γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and ethanol aqueous solution to obtain a treatment medium;

[0023] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite, heating, and stirring to obtain an intermediate material;

[0024] S4, post-processing: filtering the intermediate material, drying and crushing the filtered solids to obtain the preservative factor.

[0025] Furthermore, in S1, the mass ratio of zirconium phosphate to halloysite is 1:0.5-1.5, 1:0.6-1.4 or 1:0.7-1.3.

[0026] Furthermore, in S1, the concentration of hydrogen peroxide is 2-8wt%, 2.5-6wt% or 3-5wt%.

[0027] Furthermore, in S1, the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 0.5-2:1, 0.6-1.5:1 or 0.7-1.2:1.

[0028] Furthermore, in S1, the concentration of the inorganic acid aqueous solution is 0.005-0.2wt%, 0.08-0.18wt% or 0.1-0.15wt%.

[0029] Furthermore, in S1, the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 5-20:1, 8-15:1 or 9-12:1.

[0030] Furthermore, in S1, the inorganic acid includes at least one of hydrochloric acid, sulfuric acid, and phosphoric acid.

[0031] Furthermore, in S1, the stirring time is 2-10 hours, 3-9 hours or 4-8.5 hours.

[0032] Furthermore, in S2, the mass ratio of γ-ureidopropyltriethoxysilane to 3-aminopropyltrimethoxysilane is 1:0.4-0.8, 1:0.45-0.8 or 1:0.5-0.75.

[0033] Furthermore, in S2, the concentration of the ethanol aqueous solution is 35-50wt%, 40-50wt% or 42-48wt%.

[0034] Furthermore, in S2, the ratio of the mass of the ethanol aqueous solution to the total mass of γ-ureidopropyltriethoxysilane and 3-aminopropyltrimethoxysilane is 40-150:1, 50-140:1 or 50-120:1.

[0035] Furthermore, in S2, the stirring time is 2-10 hours, 3-9 hours or 4-8.5 hours.

[0036] Furthermore, in S3, the ratio of the mass of the treatment medium to the mass of the zirconium phosphate and halloysite composite is 10-50:1, 12-45:1 or 15-40:1.

[0037] Furthermore, in S3, the heating temperature is 30-55°C hour, 35-52°C hour or 38-50°C hour.

[0038] Furthermore, in S3, the stirring time is 2-10 hours, 3-9 hours or 4-8.5 hours.

[0039] Furthermore, the preparation method of the preservative factor comprises the following steps:

[0040] S1. Mix zirconium phosphate and halloysite in a mass ratio of 1:0.5-1.5, hydrogen peroxide with a concentration of 2-8wt% and an inorganic acid aqueous solution with a concentration of 0.005-0.2wt%, and stir for 2-10 hours, filter, dry the filtered solid, and crush to obtain a zirconium phosphate and halloysite composite; wherein the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 0.5-2:1, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 5-20:1;

[0041] S2, mixing γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane in a mass ratio of 1:0.4-0.8 with an ethanol aqueous solution with a concentration of 35-50wt% for 2-10 hours to obtain a treatment medium; wherein the ratio of the mass of the ethanol aqueous solution to the total mass of γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane is 40-150:1;

[0042] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite in a mass ratio of 10-50:1, heating to 30-55° C., stirring for 2-10 hours, to obtain an intermediate material;

[0043] S4, post-processing: filtering the intermediate material, drying and crushing the filtered solids to obtain the preservative factor.

[0044] On the other hand, the present invention also provides a method for preparing the powder coating, comprising the following steps:

[0045] (1) Weigh the raw materials;

[0046] (2) The raw materials are mixed in a mixing container, and then transported to an extruder for melt extrusion, tableting, crushing, and screening to a particle size of 5-100 microns.

[0047] On the other hand, the present invention also provides the use of the powder coating in coating petroleum pipelines.

[0048] Beneficial effects:

[0049] The present invention uses zirconium phosphate and halloysite to be treated with hydrogen peroxide and an inorganic acid aqueous solution, and then treated with a treatment medium composed of γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and an ethanol aqueous solution, and then post-treated to obtain an anti-corrosion factor. The powder coating prepared with a two-step epoxy resin, a phenolic curing agent, dimethylimidazole, a leveling agent, a brightener, a degassing agent, wollastonite and a pigment has excellent wear resistance and adhesion, good mechanical properties, and also has a strong anti-corrosion effect.

[0050] The coating prepared by the coating of the present invention has an adhesion grade of 1 when tested at 75°C for 24 hours and an adhesion grade of 2 when tested at 75°C for 28 days. The coating has a good adhesion effect and can effectively and durably protect oil pipelines.

[0051] The coating prepared by the coating of the present invention has a wear resistance of 44 mg, has high wear resistance, and can effectively prevent the surface of the oil pipeline from being damaged.

[0052] The coating prepared by the coating of the present invention passes the distilled water resistance test under 20° C. and 90 days, and no discoloration, swelling, softening, blistering, cracking or peeling occurs on the coating surface.

[0053] The coating prepared by the coating of the present invention passes the 10wt% sodium hydroxide aqueous solution resistance test under 20°C and 90d, and the coating surface does not suffer from discoloration, swelling, softening, blistering, cracking, or peeling.

[0054] The coating prepared by the coating of the present invention passes the test of resistance to a pH 2.5 hydrochloric acid aqueous solution at 20° C. for 90 days, and the coating surface does not experience discoloration, swelling, softening, blistering, cracking, or peeling.

[0055] The anticorrosion factor obtained by modifying zirconium phosphate and halloysite in the coating system of the present invention can give the coating excellent adhesion effect, wear resistance and chemical corrosion resistance; especially when the mass ratio of zirconium phosphate to halloysite is 1:0.5-1.5, the anticorrosion factor obtained by modification can give the coating better performance.

[0056] In the coating preparation system of the present invention, the use of hydrogen peroxide can increase the adhesion, wear resistance and chemical corrosion resistance of the coating; especially when the concentration of hydrogen peroxide reaches 2-8wt%, the adhesion, wear resistance and chemical corrosion resistance of the obtained coating are better.

[0057] The present invention adopts γ-urea propyl triethoxy silane and 3-aminopropyl trimethoxy silane to jointly process zirconium phosphate and halloysite, which can make it have better compatibility with the coating system and give the coating a better effect. The γ-urea propyl triethoxy silane and 3-aminopropyl trimethoxy silane used in the present invention jointly process zirconium phosphate and halloysite, which can mutually promote the wear resistance and chemical corrosion resistance of the coating. The mass ratio of the two is in the range of 1:0.4-0.8, and the coating obtained by the coating shows better performance. DETAILED DESCRIPTION

[0058] The present invention will be described below in conjunction with specific embodiments, and the effects of the present invention will be more clearly presented.

[0059] 1. Preparation of preservative factors

[0060] Antiseptic Factor 1:

[0061] The preparation method is as follows:

[0062] S1. Mix zirconium phosphate (Wuhan Kemik Biomedical Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) and halloysite (Hebei Runhuabang New Material Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) in a mass ratio of 1:1, with 4.2wt% hydrogen peroxide and 0.1wt% hydrochloric acid aqueous solution, stir at 60 rpm for 5 hours, filter with 50 nm nanofiltration membrane, dry the filtered solid at 65°C under vacuum to a water content of about 4.2%, crush and select particles with a particle size between 0.1-50 microns to obtain a zirconium phosphate and halloysite composite; wherein the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 1:1, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 12:1;

[0063] S2, stirring γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane in a mass ratio of 1:0.6 with a 45wt% ethanol aqueous solution at a speed of 70 rpm for 6 hours to obtain a treatment medium; wherein the ratio of the mass of the ethanol aqueous solution to the total mass of γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane is 100:1;

[0064] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite in a mass ratio of 25:1, heating to 38° C., stirring at 70 rpm for 4.5 hours, to obtain an intermediate material;

[0065] S4. Post-treatment: Filter the intermediate material with a 50-nanometer nanofiltration membrane, dry the filtered solids at 72° C. under vacuum to a water content of about 3.8%, and crush the particles with a particle size of 0.1-25 μm to obtain the preservative factor.

[0066] Antiseptic Factor 2:

[0067] The preparation method is as follows:

[0068] S1. Mix zirconium phosphate (Wuhan Kemik Biomedical Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) and halloysite (Hebei Runhuabang New Material Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) in a mass ratio of 1:0.5, with 2.5wt% hydrogen peroxide and 0.12wt% hydrochloric acid aqueous solution, stir at 60 rpm for 5.5 hours, filter with a 50 nm nanofiltration membrane, dry the filtered solid at 68°C under vacuum to a water content of about 4.2%, crush and select particles with a particle size between 0.1-50 microns to obtain a zirconium phosphate and halloysite composite; wherein the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 0.6:1, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 10:1;

[0069] S2, stirring γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane in a mass ratio of 1:0.7 with a 35wt% ethanol aqueous solution at a speed of 70 rpm for 6 hours to obtain a treatment medium; wherein the ratio of the mass of the ethanol aqueous solution to the total mass of γ-ureidopropyl triethoxysilane and 3-aminopropyl trimethoxysilane is 80:1;

[0070] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite in a mass ratio of 30:1, heating to 37° C., stirring at 70 rpm for 5.2 hours, to obtain an intermediate material;

[0071] S4. Post-treatment: Filter the intermediate material with a 50-nanometer nanofiltration membrane, dry the filtered solids at 72° C. under vacuum to a water content of about 3.8%, and crush the particles with a particle size of 0.1-25 μm to obtain the preservative factor.

[0072] Anticorrosion factor 3: The mass ratio of zirconium phosphate to halloysite is 1:0.1, and the others are the same as those of anticorrosion factor 1.

[0073] Anticorrosion factor 4: The mass ratio of zirconium phosphate to halloysite is 1:0.3, and the others are the same as those of anticorrosion factor 1.

[0074] Anticorrosion factor 5: The mass ratio of zirconium phosphate to halloysite is 1:2, and the rest is the same as that of anticorrosion factor 1.

[0075] Anticorrosion factor 6: The mass ratio of zirconium phosphate to halloysite is 1:4, and the rest is the same as that of anticorrosion factor 1.

[0076] Preservative Factor 7: Hydrogen peroxide is replaced with an equal amount of water. Everything else is the same as Preservative Factor 1.

[0077] Preservative factor 8: The concentration of hydrogen peroxide is 0.5wt%, and the others are the same as those of preservative factor 1.

[0078] Preservative factor 9: The concentration of hydrogen peroxide is 15wt%, and the others are the same as those of preservative factor 1.

[0079] Antiseptic Factor 10:

[0080] The preparation method is as follows:

[0081] S1. Mix zirconium phosphate (Wuhan Kemik Biomedical Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) and halloysite (Hebei Runhuabang New Material Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) in a mass ratio of 1:1, with 4.2wt% hydrogen peroxide and 0.1wt% hydrochloric acid aqueous solution, stir at 60 rpm for 5 hours, filter with 50 nm nanofiltration membrane, dry the filtered solid at 65°C under vacuum to a water content of about 4.2%, crush and select particles with a particle size between 0.1-50 microns to obtain a zirconium phosphate and halloysite composite; wherein the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 1:1, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 12:1;

[0082] S2, stirring γ-ureidopropyltriethoxysilane and 45wt% ethanol aqueous solution at a rotation speed of 70 rpm for 6 hours to obtain a treatment medium; wherein the mass ratio of the ethanol aqueous solution to the mass of the γ-ureidopropyltriethoxysilane is 100:1;

[0083] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite in a mass ratio of 25:1, heating to 38° C., stirring at 70 rpm for 4.5 hours, to obtain an intermediate material;

[0084] S4. Post-treatment: Filter the intermediate material with a 50-nanometer nanofiltration membrane, dry the filtered solids at 72° C. under vacuum to a water content of about 3.8%, and crush the particles with a particle size of 0.1-25 μm to obtain the preservative factor.

[0085] Antiseptic Factor 11:

[0086] The preparation method is as follows:

[0087] S1. Mix zirconium phosphate (Wuhan Kemik Biomedical Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) and halloysite (Hebei Runhuabang New Material Technology Co., Ltd., screened particle size 0.1-100 microns, the same below) in a mass ratio of 1:1, with 4.2wt% hydrogen peroxide and 0.1wt% hydrochloric acid aqueous solution, stir at 60 rpm for 5 hours, filter with 50 nm nanofiltration membrane, dry the filtered solid at 65°C under vacuum to a water content of about 4.2%, crush and select particles with a particle size between 0.1-50 microns to obtain a zirconium phosphate and halloysite composite; wherein the ratio of the mass of hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 1:1, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 12:1;

[0088] S2, stirring 3-aminopropyltrimethoxysilane and a 45wt% ethanol aqueous solution at a rotation speed of 70 rpm for 6 hours to obtain a treatment medium; wherein the ratio of the mass of the ethanol aqueous solution to the mass of the 3-aminopropyltrimethoxysilane is 100:1;

[0089] S3, mixing the treatment medium with the zirconium phosphate and halloysite composite in a mass ratio of 25:1, heating to 38° C., stirring at 70 rpm for 4.5 hours, to obtain an intermediate material;

[0090] S4. Post-treatment: Filter the intermediate material with a 50-nanometer nanofiltration membrane, dry the filtered solids at 72° C. under vacuum to a water content of about 3.8%, and crush the particles with a particle size of 0.1-25 μm to obtain the preservative factor.

[0091] Anticorrosion factor 12: The mass ratio of γ-ureidopropyltriethoxysilane and 3-aminopropyltrimethoxysilane is 1:0.2, and the rest are the same as those of anticorrosion factor 1.

[0092] Anticorrosion factor 13: The mass ratio of γ-ureidopropyltriethoxysilane and 3-aminopropyltrimethoxysilane is 1:1.1, and the rest are the same as those of anticorrosion factor 1.

[0093] 2. Preparation of powder coating

[0094] Paint 1:

[0095] The preparation process is as follows:

[0096] (1) Weigh the following raw materials by mass: 620 parts of two-step epoxy resin, 140 parts of phenolic curing agent, 4.2 parts of dimethylimidazole, 7 parts of leveling agent, 4.1 parts of brightener, 3.5 parts of degassing agent, 200 parts of wollastonite, 17.3 parts of anticorrosive factor and 103.9 parts of pigment;

[0097] (2) The raw materials are mixed in a mixing container, and then transported to an extruder, and melt-extruded at a temperature of 94.2° C. and a screw speed of 40 Hz, and then tableted and crushed to screen a particle size of 5-100 μm to obtain the powder coating;

[0098] Two-step epoxy resin: Brand: Nan Ya, Taiwan, China, Model: NPSN-901X75.

[0099] Phenolic curing agent: 2,4,6-tris(dimethylaminomethyl)phenol;

[0100] Leveling agent: BYK-371 from Germany;

[0101] Brightener: Japan Shin-Etsu KP-366;

[0102] Degassing agent: Degassing agent KT961;

[0103] Wollastonite: Shandong Wenqi New Materials Co., Ltd., screened particle size 5-70 μm;

[0104] Antiseptic factor: Antiseptic factor 1 as above;

[0105] Pigment: Titanium dioxide and red iron oxide are mixed in a mass ratio of 22:1, and both are screened to have a particle size between 10-30 microns.

[0106] Paint 2:

[0107] The preparation process is as follows:

[0108] (1) Weigh the following raw materials by mass: 630 parts of two-step epoxy resin, 145 parts of phenolic curing agent, 4.5 parts of dimethylimidazole, 7.2 parts of leveling agent, 4.0 parts of brightener, 3.8 parts of degassing agent, 210 parts of wollastonite, 17.4 parts of anticorrosive factor and 105 parts of pigment;

[0109] (2) The raw materials are mixed in a mixing container, and then transported to an extruder, and melt-extruded at a temperature of 94.2° C. and a screw speed of 40 Hz, and then tableted and crushed to screen a particle size of 5-100 μm to obtain the powder coating;

[0110] Two-step epoxy resin: NPSN-901X75;

[0111] Phenolic curing agent: p-diphenol and 2,4,6-tris(dimethylaminomethyl)phenol are mixed in a mass ratio of 1:0.5;

[0112] Leveling agent: BYK-333 from Germany;

[0113] Brightener: Japan Shin-Etsu KP-366;

[0114] Degassing agent: Degassing agent KT961;

[0115] Wollastonite: Shandong Wenqi New Materials Co., Ltd., screened particle size 5-70 μm;

[0116] Antiseptic factor: Antiseptic factor 2 as above;

[0117] Pigment: Titanium dioxide and red iron oxide are mixed in a mass ratio of 22:1, and both are screened to have a particle size between 10-30 microns.

[0118] Coating 3-13: Coating 3-13 uses preservative factor 3-13 to replace preservative factor 1 in coating 1, and the rest is the same as coating 1.

[0119] 3. Effect Test

[0120] The coatings 1-13 were sprayed on the steel pipe and cured at 220°C for 35 minutes to obtain a coating with a thickness of about 350 microns. The coating was placed at room temperature for two days before the effect test. The effect test results are shown in Tables 1-2; Table 1 is the adhesion and wear resistance effect test, Table 2 is the chemical corrosion resistance effect test, and the 90d pass test in Table 2 indicates that the coating after 90 days has no discoloration, bulging, softening, blistering, cracking, or peeling.

[0121] Table 1: Adhesion and abrasion resistance test

[0122]

[0123] Table 2: Chemical corrosion resistance test

[0124]

[0125] From the test results in the above table, it can be obtained that the present invention uses zirconium phosphate and halloysite to be treated with hydrogen peroxide and inorganic acid aqueous solution, and then treated with a treatment medium composed of γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and ethanol aqueous solution, and then post-treated to obtain an anti-corrosion factor. The powder coating prepared with a two-step epoxy resin, a phenolic curing agent, dimethylimidazole, a leveling agent, a brightener, a degassing agent, wollastonite and a pigment has excellent wear resistance and adhesion, good mechanical properties; and also has a strong anti-corrosion effect.

[0126] The coating prepared by the coating of the present invention has an adhesion grade of 1 when tested at 75°C for 24 hours and an adhesion grade of 2 when tested at 75°C for 28 days. The coating has a good adhesion effect and can effectively and durably protect oil pipelines.

[0127] The coating prepared by the coating of the present invention has a wear resistance of 44 mg, has high wear resistance, and can effectively prevent the surface of the oil pipeline from being damaged.

[0128] The coating prepared by the coating of the present invention passes the distilled water resistance test under 20° C. and 90 days, and no discoloration, swelling, softening, blistering, cracking or peeling occurs on the coating surface.

[0129] The coating prepared by the coating of the present invention passes the 10wt% sodium hydroxide aqueous solution resistance test under 20°C and 90d, and the coating surface does not suffer from discoloration, swelling, softening, blistering, cracking, or peeling.

[0130] The coating prepared by the coating of the present invention passes the test of resistance to a pH 2.5 hydrochloric acid aqueous solution at 20° C. for 90 days, and the coating surface does not experience discoloration, swelling, softening, blistering, cracking, or peeling.

[0131] It can be seen from the test results of coatings 1, 3-6 that the anti-corrosion factor obtained by modifying zirconium phosphate and halloysite in the coating system of the present invention can give the coating excellent adhesion, wear resistance and chemical corrosion resistance; especially when the mass ratio of zirconium phosphate and halloysite is 1:0.5-1.5, the anti-corrosion factor obtained by modification can give the coating better performance.

[0132] The test results of coatings 1, 7-9 show that in the coating preparation system of the present invention, the use of hydrogen peroxide can increase the adhesion, wear resistance and chemical corrosion resistance of the coating; especially when the concentration of hydrogen peroxide reaches 2-8wt%, the adhesion, wear resistance and chemical corrosion resistance of the obtained coating are better.

[0133] The present invention adopts γ-urea propyl triethoxy silane and 3-aminopropyl trimethoxy silane to jointly treat zirconium phosphate and halloysite, which can make it have better compatibility with the coating system and give the coating a better effect. According to the test results of coatings 1 and 10-11, γ-urea propyl triethoxy silane and 3-aminopropyl trimethoxy silane jointly treat zirconium phosphate and halloysite, which can mutually promote the wear resistance and chemical corrosion resistance of the coating. The mass ratio of the two is in the range of 1:0.4-0.8, and the coating obtained by the coating shows better performance.

[0134] Those skilled in the art may make various changes and modifications to the present invention. If these changes and modifications fall within the scope of the claims of the present invention and their equivalents, the present invention is intended to include these changes and modifications.

Claims

1. A heavy-duty anti-corrosion petroleum pipeline powder coating, characterized in that: The preparation material comprises the following raw materials in parts by weight: 550-750 parts of two-step epoxy resin, 100-170 parts of phenolic curing agent, 2-10 parts of dimethyl imidazole, 5-15 parts of leveling agent, 1-8 parts of brightener, 1-5 parts of degassing agent, 150-300 parts of wollastonite, 8-40 parts of antiseptic factor and 50-200 parts of pigment; The preparation method of the preservative factor comprises the following steps: S1, mixing zirconium phosphate, halloysite, hydrogen peroxide, and an inorganic acid aqueous solution, filtering, drying, and crushing the filtered solid to obtain a zirconium phosphate and halloysite composite; S2, stirring and mixing γ-ureidopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and ethanol aqueous solution to obtain a treatment medium; S3, mixing the treatment medium with the zirconium phosphate and halloysite composite, heating, and stirring to obtain an intermediate material; S4, post-processing: filtering the intermediate material, drying and crushing the filtered solids to obtain the preservative factor; In S1, the mass ratio of zirconium phosphate to halloysite is 1:0.5-1.5; In S2, the mass ratio of γ-ureidopropyltriethoxysilane to 3-aminopropyltrimethoxysilane is 1:0.4-0.8; In the S1, the concentration of hydrogen peroxide is 2-8wt%.

2. The powder coating according to claim 1, characterized in that The phenolic curing agent is at least one of diphenol propane, 2,4,6-tris(dimethylaminomethyl)phenol, resorcinol and catechol.

3. The powder coating according to claim 1, characterized in that The leveling agent includes at least one of silicone, acrylate and fluorocarbon compounds.

4. The powder coating according to claim 1, characterized in that The pigment comprises at least one of titanium dioxide, zinc oxide, lithopone, red iron oxide, toluidine red, scarlet powder and cadmium red.

5. The powder coating according to claim 1, characterized in that The preparation material comprises the following parts: 600-660 parts of two-step epoxy resin, 130-150 parts of phenolic curing agent, 3-5 parts of dimethyl imidazole, 6-8 parts of leveling agent, 3-5 parts of brightening agent, 2-4 parts of degassing agent, 180-240 parts of wollastonite, 12-25 parts of antiseptic factor and 80-180 parts of pigment.

6. The powder coating according to claim 1, characterized in that The ratio of the hydrogen peroxide to the mass of zirconium phosphate and the total mass of halloysite is 0.5-2:1; And / or, the concentration of the inorganic acid aqueous solution is 0.005-0.2wt%, and the ratio of the mass of the inorganic acid aqueous solution to the total mass of zirconium phosphate and halloysite is 5-50:

1.

7. The powder coating according to claim 1, characterized in that In S2, the concentration of the ethanol aqueous solution is 35-50wt%, and the ratio of the mass of the ethanol aqueous solution to the total mass of γ-ureidopropyltriethoxysilane and 3-aminopropyltrimethoxysilane is 40-150:1; And / or, in S3, the ratio of the mass of the treatment medium to the mass of the zirconium phosphate and halloysite composite is 10-50:

1.

8. The method for preparing a powder coating according to any one of claims 1 to 7, characterized in that: The steps include: (1) Weigh the raw materials; (2) The raw materials are mixed in a mixing container, and then transported to an extruder for melt extrusion, tableting, crushing, and screening to a particle size of 5-100 microns.

9. Use of the powder coating according to any one of claims 1 to 7 in coating petroleum pipelines.

Citation Information

Patent Citations

  • Antistatic powder coating as well as preparation method and application thereof

    CN117701108A

  • Sound-absorbing powder coating and preparation method thereof

    CN117801623A